Quality of Life and Sexual Function of Patients Following Radical Hysterectomy and Vaginal Extension. (1st May 2014) - Ye, Shuang; Yang, Jiaxin; Cao, Dongyan; Zhu, Lan; Lang, Jinghe; Chuang, Linus T.; Shen, Keng
Abstract: Introduction: Radical hysterectomy (RH) has negative consequences on sexual function due to a shortened vagina, vaginal dryness, and dyspareunia. Peritoneovaginoplasty aims to extend vagina by vesical peritoneum and anterior rectal wall to improve postoperative sexual function. Aim: The aim of this study was to investigate whether vaginal extension can improve sexual function and quality of life and the problem of sexual dysfunction in early-stage cervical cancer survivors (CCSs) in China. Methods: Case-control and questionnaire-based methods were employed. Thirty-one patients who had undergone vaginal extension following RH and 28 patients with matching factors after RH alone were enrolled in the study. Main Outcome Measures: Both groups were assessed retrospectively by questionnaires at least 6 months after treatment. The European Organization for Research and Treatment of Cancer Quality-of-Life questionnaire cervical cancer module and the Sexual Function Vaginal Changes Questionnaire are validated measurements for disease- and treatment-specific issues. Results: Vaginal length was 10.03 ± 1.26 cm and 5.92 ± 1.05 cm in study and control group, respectively ( P < 0.05). In the study group, 67.7% patients and 64.3% of control group resumed sexual activity at the time of interview, averaging 6 months between treatment and sexual activity. While difficulty emptying bladder, incomplete emptying, and constipation were the most commonly reported symptoms, no significant difference was observed regarding pelvic floor symptoms. Reduced vagina size and shortened vagina was significantly more prominent in the control group, whereas both group presented with hypoactive sexual desire (88.1%), orgasm dysfunction (71.8%), and low enjoyment or relaxation after sex (51.3%). Conclusion: Shortened vagina was significantly less reported in study group, while no difference was observed in other sex-related dimensions. Vaginal extension does not worsen pelvic floor symptoms. Sexual rehabilitation interventions are of significance and should be paid more attention to the CCSs in China.